Brucellosis-induced peritonitis and abdominal aortitis in a non-endemic area patient on peritoneal dialysis: a case report and literature review - Huang, Yiqi; Zhu, Xingyu; Shen, Weigang; Wang, Yueping; Han, Meixiang (Frontiers in Medicine, 2024)
Background Brucella infection is uncommon among peritoneal dialysis (PD) patients in non-endemic areas, and the occurrence of both peritonitis and abdominal aortitis is rare. Case presentation In December 2023, a 63-year-old male patient undergoing PD was admitted to Shaoxing Second Hospital due to fever, abdominal pain, and cloudy dialysate. Upon physical examination, diffuse mild abdominal pain and tenderness were observed. Subsequent investigation into the patient's medical history revealed consumption of freshly slaughtered lamb from local farmers 3 days prior to the onset of symptoms. Various diagnostic tests, including routine blood tests, procalcitonin levels, and PD fluid analysis, indicated the presence of infection. Abdominal computed tomography (CT) imaging revealed localized lumen widening of the abdominal aorta with surrounding exudative changes. On the sixth day in the hospital, blood and PD fluid cultures confirmed Brucella melitensis infection. The patient was diagnosed with brucella-associated peritonitis and aortitis. Treatment was adjusted to include rifampin and doxycycline for 6 weeks, and the decision was made to keep the PD catheter. Remarkably, the patient exhibited resolution of peritonitis and abdominal aortitis within the initial week of the adjusted treatment. Currently, the patient continues to receive ongoing clinical monitoring. Conclusion Brucella is rare but can cause PD-associated peritonitis and arteritis. Prompt diagnosis and treatment can lead to a good outcome in PD patients. Dual therapy is effective, but the need for catheter removal is unclear. Consider international guidelines and patient factors when deciding on catheter removal.